Features of Heavy Metals Accumulation in Bottom Sediments of the Southern Bug Hydroecosystem - Olena Mitryasova (Journal of Ecological Engineering, 2020)
The provided studies allowed determining the peculiarities of heavy metals accumulation in the sediments, as well as the nature of their distribution in the hydroecosystem Southern Bug (Ukraine). Geochemical anomalies are formed in the zones of influence of industrial and urban agglomerations. Technogenic pollutions of bottom sediments with heavy metals affects to qualitative state of the water environment and can cause cumulative toxicosis on the hydrobionts population in zones of geochemical anomalies formation, namely in the area of influence of the Nova Odessa and Mykolaiv cities. The mechanism of the emergence of cumulative toxicosis is accompanied by chronic effects of low concentrations on hydrobionts with an excess of permissible fluctuations on a regional background, which ultimately provokes the development of intoxication.